2020
DOI: 10.4103/jrpp.jrpp_20_53
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the efficacy of levetiracetam and carbamazepine in the treatment of rolandic seizures in children: An open-label randomized controlled trial

Abstract: Objective: This study was performed to investigate whether levetiracetam should be preferred to carbamazepine as a treatment choice for benign childhood epilepsy with centro Temporal spikes (BCECTS), the most common partial epilepsy of childhood. Methods: This randomized clinical trial study included 92 children with rolandic epilepsy aged 4–12 years referred to the Pediatric Neurology Clinic at Imam Hossein Hospital, Isfahan, Iran, from April 2019 to January 2020. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Other countries recommend levetiracetam, carbamazepine, sodium valporate, oxcarbazepine, and lamotrigine as first-line drugs (9). Similar to our findings, levetiracetam is more preferred due to its efficacy (in seizure control, EEG normalization, cognition, speech, and behavior) and less side effects (10)(11)(12)(13)(14). In this study, levetiracetam plus sodium valproate showed statistically significant association with reduction of SWI.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Other countries recommend levetiracetam, carbamazepine, sodium valporate, oxcarbazepine, and lamotrigine as first-line drugs (9). Similar to our findings, levetiracetam is more preferred due to its efficacy (in seizure control, EEG normalization, cognition, speech, and behavior) and less side effects (10)(11)(12)(13)(14). In this study, levetiracetam plus sodium valproate showed statistically significant association with reduction of SWI.…”
Section: Discussionsupporting
confidence: 88%
“…Several countries recommend the utilization of levetiracetam, carbamazepine, sodium valproate, oxcarbazepine, and lamotrigine as first-line drugs (9). Levetiracetam is more preferred due to its efficacy (in seizure control, EEG normalization, cognition, speech, and behavior) and less side effects (10)(11)(12)(13)(14). Moreover, as monotherapy, it has been shown to be effective even in other idiopathic generalized epilepsy, such as in the absence epilepsy and juvenile myoclonic epilepsy (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding treatment, recent study from Iran[ 11 ] proposed levetiracetam as monotherapy as an alternative to carbamazepine which can cause side effects such as skin rash and intolerance. However, we used carbamazepine alone in 58.62% of our cases without side effects and levetiracetam is more expensive.…”
Section: Discussionmentioning
confidence: 99%
“…In these trials, LEV monotherapy's e cacy in children is almost equally comparable to other AEDs, specially CBZ as rst-line therapy. Also, they recommended conducting RCTs with larger sample sizes to compare the e cacy and adverse effects of LEV monotherapy in children more accurately (18,19). Due to the limited number of comparing trials on LEV and CBZ monotherapy and the importance of choosing a suitable drug for controlling pediatric focal seizures, this randomized clinical trial was conducted in children with focal epilepsy to investigate and evaluate the e cacy and side effects of both therapies.…”
Section: Introductionmentioning
confidence: 99%